2009
DOI: 10.1002/art.24757
|View full text |Cite
|
Sign up to set email alerts
|

Vascular cell adhesion molecule 1 as a predictor of severe osteoarthritis of the hip and knee joints

Abstract: Objective. Osteoarthritis (OA) is a leading cause of pain and physical disability in middle-aged and older individuals. We undertook this study to determine predictors of the development of severe OA, apart from age and overweight.Methods. Joint replacement surgery due to severe hip or knee OA was recorded over a 15-year period in the prospective Bruneck cohort study. Demographic characteristics and lifestyle and biochemical variables, including the level of soluble vascular cell adhesion molecule 1 (VCAM-1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 87 publications
8
93
0
2
Order By: Relevance
“…In accord with other emerging data that vascular pathology may play a role in the pathogenesis of osteoarthritis [26], adults with hip osteoarthritis disability and one or more comorbid vascular health conditions studied here were more disabled than those without vascular pathology. In addition, many of these cases had higher body mass indices on average than those with no comorbid cardiovascular health condition.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In accord with other emerging data that vascular pathology may play a role in the pathogenesis of osteoarthritis [26], adults with hip osteoarthritis disability and one or more comorbid vascular health conditions studied here were more disabled than those without vascular pathology. In addition, many of these cases had higher body mass indices on average than those with no comorbid cardiovascular health condition.…”
Section: Resultssupporting
confidence: 90%
“…Other research similarly emphasizes the importance of early detection and secondary prevention of all cardiovascular problems, to prevent future worsening of activity limitations [2], huge additional medical costs [17] and based on early studies, the risk for developing osteoarthritis [21][See Fig. 1 [30] Moreover, if the level of soluble vascular cell adhesion molecule (VCAM-1) is a possible predictor of severe hip osteoarthritis, and atherosclerosis and thrombosis as well as inflammation [26], sub groups with a high level of this factor might be selectively targeted. In the interim, it is recognized that the present cohort may not represent all cases with condition; not all data were available or complete; and the use of chart reviews to explore temporal trends and interactions and understand mediating or moderating factors influencing hip osteoarthritis disability may not be without limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven ''progression'' studies [7-9, 15, 17, 24, 29, 30, 35, 37, 39] investigated the association of 13 different biomarker levels with the progression of hip OA. Of the 11 studies, four looked at progression of known hip OA [9,15,37,39]; three studies investigated the progression to incident hip OA from unspecified prearthritic hip disease [8,17,29]; and four studies investigated both OA progression and incidence [7,24,30,35]. Duration of followup to evaluate OA progression ranged from 1 year to 15 years.…”
Section: Literature Searchmentioning
confidence: 99%
“…[21] Other studies also reported the elevated level of soluble VCAM-1 in serum of patients with osteoarthritis. [22][23][24] In joints, VCAM-1 is expressed by microvascular endothelial cells, synovial fibroblasts, and chondrocytes. [25] It is not appreciably expressed on resting vascular endothelium but is rapidly induced in response to a number of inflammatory stimuli, such as TNF-a, IL-1β.…”
Section: Discussionmentioning
confidence: 99%